Study of prevalence of ocular manifestations in HIV positive patients - Saini, Nishtha; Hasija, Sonia; Kaur, Prempal; Kaur, Manpreet; Pathania, Vishal; Singh, Ajeet (Nepalese Journal of Ophthalmology, 2019)
Introduction: HIV/AIDS is a disorder which affects multiple systems in our body but ophthalmic manifestations do occur in 70-80% of patients sometime during their lifetime. Eye is affected either directly by HIV virus or indirectly through various opportunistic infections. HIV related ophthalmic manifestations are wide and can affect any part of eye from a dnexal disorders to posterior segment diseases including the optic nerve and the optic tract. This study was done to know the prevalence of ocular manifestations in the known HIV positive case & to correlate the ocular manifestations in HIV positive patients with their CD4+ lymphocyte count and duration of disease. Material & Methods: In the present study, we examined 200 known cases of HIV infection who attended the Out Patient Department of Government Eye Hospital, Amritsar, Punjab. Detailed ocular examination was done and the findings were correlated with CD4+ count and duration of the disease. Result: In the present study it was found that dry eye and HIV retinopathy were amongst the most common ocular manifestations accounting for 20.5% and 20% of the total cases. Next in the series was neuro ophthalmic complications which include dpapilledema, optic nerve atrophy, papillitis and also third nerve abnormalities. It consisted of 5.5% of the total cases. Almost equal in incidence was anterior uveitis consisting of 5% of the total. Next of importance was CMV retinitis of which 5 cases were seen which constituted 2.5% of the total and all these cases were observed in the patients with CD4+ count less than 50/mm3. p value for this was 0.008 which was statistically significant. Few cases of blephar it is, conjunctivitis, cellulitis, herpes zoster ophthalmic us and keratitis were also found which consisted of 2.5%, 0.5%, 1%,3%, and 2% respectively. Conclusion: Any HIV-infected person who at any stage experiences ocular symptoms also should get competent ophthalmologic care at the earliest. Any delay in treatment can lead to permanent visual loss. An improved coordination between two branches of ophthalmology and HIV medicine will need long coordination against this dreadful disease.